Are High-Altitude Residents More Susceptible to Covid-19 in India? Findings and Potential Implications for Research and Policy. (October 2022) - Chakraborty, Sushmita; Das, Upasak; Rathore, Udayan; Sarkhel, Prasenjit
In this paper, we study the incidence of COVID-19 and the associated fatality with altitude using high frequency, district level data from India. To understand the implications of the nationwide lockdown after the outbreak, we use data for about four months- two from the lockdown period starting from March 25 till May 31, 2020 and about two months after unlocking was initiated (June 1-July 26, 2020). The multivariate regression result indicates slower growth in average rate of infection during the lockdown period in hilly regions, the gains of which attenuated after the unlocking was initiated. Despite these early gains, the rate of fatalities is significantly higher during the lockdown period in comparison to the plains. The findings remain robust to multiple alternative specifications and methods including one that accounts for confounding possibilities via unobservable and provides consistent estimates of bias adjusted treatment effects. The evidence supports the need for provisioning of public health services and infrastructure upgradation, especially maintenance of adequate stock of life support devices, in high altitude regions. It also underscores the necessity for strengthening and revising the existing Hill Areas Development Programme and integrating important aspects of public health as part of this policy.